Classification of the soils of river Island micro-depressions (Great War Island, Serbia) - Radmanović Svjetlana B.; Bogosavljević Jelena P.; Dugonjić Mladen D.; Đorđević Aleksandar R. (Journal of Agricultural Sciences (Belgrade))
Great War Island (GWI) is a river island formed at the confluence of the Sava and Danube rivers, heavily exposed to groundwater and flooding and is therefore suitable as a case study for the investigation of hydromorphic soils. The aim of this study was to classify the soils in two different micro-depression on Great War Island according to the local (Škorić 1985) and international (WRB 2022 and USDA Soil Taxonomy 1999) systems, with particular attention to the soil-forming factors that influenced the classification of the soils. The results obtained could help to improve the existing local classification system or to create a new system in the future. The soil of the closed (less flooded) micro-depression is Eugley, Hipogley, Mineral, Calcareous (Škorić 1985) or Calcaric Oxygleyic Gleysol (Loamic, Humic) (WRB 2022). The soil of the micro-depression open to the Danube (more flooded) is Humogley, Calcareous, Weakly alkalized, Loamy (Škorić 1985) or Calcaric Oxygleyic Mollic Tidalic Gleysol (Loamic, FluviLoaminovic) (WRB 2022). The both soils are Typic Endoaquolls (USDA Soil Taxonomy 1999). The high level and amplitude of the groundwater and the duration of the flood caused by the topography, as well as the texture of the alluvial sediments, are the main soil-forming factors that have influenced the classification of the soils. The local soil classification mostly corresponds to the two international soil classifications with regard to the influence of pedogenetic factors/characteristics. To increase its accuracy, quantitative thresholds for soil type and lower levels are required.